MANIPULATION OF DOMESTIC VIOLENCE RESPONSE TOOLS: THE PROBLEM OF FALSE REPORTS AND ABUSE OF SPECIAL MEASURES (Bulletin of criminological association of Ukraine, 2025)
The article examines the categories of tools used to combat domestic violence. It explores the issue of deliberately false reports of domestic violence, which are submitted not to protect the victim, but to gain personal or procedural advantages. Typical methods of abuse in this area are identified, such as initiating the issuance of an emergency restraining order or a protective order with the aim of evicting a person from the residence, restricting communication with a child, or influencing divorce and property division proceedings. Common forms of such abuse are outlined.
Keywords: domestic violence; combating domestic violence; tools for countering domestic violence; abuse of victims’ rights; false reports; emergency restraining order; protective order